Paraneoplastic optic neuropathy secondary to adenocarcinoma of the lung - Yap, Jin Yi; Wan-Hazabbah Wan HItam; Sanihah Abdul Halim; Nurul Ain Masnon (BMJ Publishing Group, 2021)
We describe an uncommon cause of paraneoplastic optic neuropathy in adenocarcinoma of the lung. A 45-year-old healthy woman presented with seizure and encephalitis, followed by an acute visual loss in both eyes for 1 week. Her visual acuity was no perception of light in the right eye and hand movement in the left eye. There was a generalised restriction of extraocular muscle movements in both eyes. Funduscopy showed a bilateral pale optic disc. A paraneoplastic antigen autoimmune profile showed a positive anti-CV2/CRMP-5 antibody. CT of the thorax revealed the presence of right apical lung mass, confirmed to be adenocarcinoma through a biopsy. She was scheduled for lung lobectomy and chemotherapy. Unfortunately, her health deteriorated and she passed away eventually.